Pemberdayaan UMKM Desa Cimangkok Melalui Transformasi Digital Marketing: Inovasi Teknologi Untuk Kemajuan Ekonomi Kerakyatan - Neni Rosmiati; Joko Joko; Virania Indriani; Larasati Larasati; Jenal Mutaqin; Deni Sepiyan; Andreas Dwi Santoso (CV. Era Digital Nusantara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute the backbone of Indonesia's economy, contributing 61.07% to the national GDP. However, most MSMEs still face challenges in marketing aspects, particularly in adopting digital technology to expand market reach. This community service activity aims to enhance the capacity of MSME practitioners in Cimangkok Village in utilizing digital technology innovation for more effective marketing strategies. The implementation method employed a participatory approach through interactive seminars, practical workshops, and group discussions involving 35 MSME practitioners with various types of businesses. The activity was conducted in three stages: preparation (survey and coordination), implementation (seminar and workshop), and evaluation and follow-up. Evaluation results showed a significant increase in participants' understanding of digital marketing from an average score of 4.2 to 7.8 in pre-test and post-test assessments. As many as 71% of participants immediately implemented the acquired knowledge by initiating digital marketing activities, and several reported sales increases in the first week. This activity proves that digital transformation of MSMEs at the village level is highly feasible with appropriate guidance. Sustainability programs through WhatsApp groups and periodic mentoring serve as key factors to ensure long-term impacts on village economy and MSME practitioners' welfare.